Outmoded "Modernistic Effects"? (KULT_online, 2011)
This anthology analyses Annette von Droste-Hülshoffs complex handling of traditions. As the 16 essays point out, the often attested backwardness of the author, and the resulting heterogeneous assemblage of genres and forms, nevertheless create modernistic effects (p. 10). These result not from a radical separation from the past, but rather from a creative transformation of the tradition. The broad spectrum of interpretations in this anthology covers different genres (including 'semi-literary' texts such as "Westphälische Schilderungen") and creative periods (from Droste's early work, "Bertha oder die Alpen", to one of her last poems, "Lebt wohl"). Furthermore, some papers analyse her work from a cultural perspective, taking into account the discussion of scientific discourses (such as magnetism or legal history) as well as religious issues.